Methods for Film Synthesis and Coating Procedures 2020
DOI: 10.5772/intechopen.86806
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation and Wear Resistant Bi-Layer Coating for Turbocharger Housing

Abstract: An upsurge in the demand of higher power generation has been observed in the last few decades. Consequently, the mechanical components of power generation are forced to operate in the extreme working conditions for longer duration, which results in the accelerated wear and corrosion of the material. Conventional material such as grey cast iron (GCI) is a preferred material of components used for power generation at high temperature. Grey cast iron exhibits poor wear and corrosion resistance at high temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Surface properties of hardness, wear and high temperature oxidation determine the quality and surface finish of the steel product. Surface coatings are applied by thermal spray processes to develop specific surface functionalities so that the rolls can operate under these harsh operating environments [ 67 , 68 ]. Chromium has been considered for bridle rolls owing to its surface profile of domed grains, which provides an optimum surface roughness to prevent slippage without degrading the surface properties of the bridle rolls.…”
Section: Thermal Spray Applications In Iron and Steel Industrymentioning
confidence: 99%
“…Surface properties of hardness, wear and high temperature oxidation determine the quality and surface finish of the steel product. Surface coatings are applied by thermal spray processes to develop specific surface functionalities so that the rolls can operate under these harsh operating environments [ 67 , 68 ]. Chromium has been considered for bridle rolls owing to its surface profile of domed grains, which provides an optimum surface roughness to prevent slippage without degrading the surface properties of the bridle rolls.…”
Section: Thermal Spray Applications In Iron and Steel Industrymentioning
confidence: 99%
“…Oxidation occurs when metals/alloys are exposed to oxygen/air [1]. It also results in the formation of porous and noncoherent oxides, which leads to the failure of the component [2]. The dispersion of oxygen on the equipment surfaces leads to oxidation, which then propagates into the core of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Various coatings can be used to subvert the oxidation phenomenon. For instance, Vasudev et al [2] explored the use of superalloys (Inconel 718) for enhancing the elevated-temperature oxidation resistance of turbocharger housing. Inconel 718 exhibited resistance to hightemperature oxidation and erosion due to the formation of protective oxides such as nickel chromite (NiCr 2 O 4 ), chromium oxide (Cr 2 O 3 ) and aluminium oxide (Al 2 O 3 ) at an elevated temperature of 900 • C. Feng et al [3] also investigated the high-temperature oxidation resistance of laser-cladded coatings and concluded that protective oxides prevented the diffusion of oxygen into the coating layer.…”
Section: Introductionmentioning
confidence: 99%